Revitalizing Early Childhood Creativity through the Integration of Animated Videos in Problem Based Learning and Project Based Learning - Annisa Rahmi, Indah; Rakimahwati (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Early childhood creativity is a crucial developmental outcome that can be fostered through the strategic integration of appropriate pedagogical models and digital learning media. This study examines the effect of animated video media on children’s creativity when integrated with Problem Based Learning and Project Based Learning approaches. A quantitative experimental design was employed, and the data were analyzed using analysis of variance to examine both main and interaction effects. The findings reveal that the use of animated video media has a statistically significant effect on children’s creativity within both instructional approaches (p < 0.05). However, no statistically significant difference was identified between the two learning models (p > 0.05), nor was a significant interaction detected between the instructional models and the use of animated video media (p > 0.05). These results suggest that both pedagogical approaches function comparably in supporting creativity development when combined with animated video media. Conceptually, this study reinforces the role of multimedia-supported, student-centered learning environments in early childhood education and contributes empirical evidence to discussions on instructional model equivalence in fostering creative capacities. The findings also provide a theoretical basis for future research on optimizing digital media integration to support creativity development in early childhood contexts.